Analysis of Amino Acids and Related Compounds by Capillary Electrophoresis. Issue 2 (3rd April 2017) - Denoroy, Luc; Parrot, Sandrine
Abstract : For more than two decades, capillary electrophoresis (CE) was found to be a powerful tool in the separation of low molecular weight charged compounds, such as amino acids (AA). This article provides an overview on the current status of CE for analyzing AAs and their metabolites in biological and nonbiological samples. A survey of works published during the last 20 years is presented, underlining the main advantages brought by CE for the study of AAs and their amine metabolites, such as catecholamines, indolamines, histamine and other monoamines, as well as aminothiols. Sample preparation (including derivatization and concentration) and separation protocols were covered. Most AAs lack a strong UV chromophore, so the different detectors used in CE for their detection were described, including classical UV-Vis spectrophotometry, laser-induced fluorescence, mass spectrometry, electrochemistry, conductometry and chemiluminescence. The applications in life science and biotechnology were summarized. The advantages and limitations of CE analysis for AAs and future developments in this field were tentatively discussed.